Quality Assessment of Meat via Pomegranate (Punica Granatum L.) Waste-Enriched Chicken Feed - Bano, Yasmeen; Abdul Rasheed; Esha Tir Razia; Rafique, Mariyam; Muhammad, Bakht; Ahmad, Fraz; Azeem, Muhammad Shoaib; Gohar, Sabeen; Kashif, Ali Sher (Indus Journal of Bioscience Research, 2024)
This study aimed to assess the impact of dietary supplementation with pomegranate seed powder (PSP) on the growth performance and meat quality of broiler chickens while exploring its potential as an environmentally friendly feed additive. A total of 120 Cobb broiler chicks were randomly assigned to four dietary treatments: PSP0 (Control, 0% PSP), PSP1 (0.5% PSP), PSP2 (1% PSP), and PSP3 (1.5% PSP), with five replicates of eight birds per group. PSP supplementation was administered during weeks 4 and 5 of the growth period, and growth performance, carcass quality, and meat attributes were evaluated. The results showed that in week 4, PSP3 increased average weekly feed intake (AWFI) and feed conversion ratio (FCR), while in week 5, PSP2 improved live bird weight (LBW) compared to the control. However, body weight gain (BWG) and organ weights of various carcass components, including breast, heart, liver, drumstick, thigh, and neck, remained non-significant across all groups. Meat quality analysis revealed no significant effects of PSP on fat content, pH, moisture, ash, or instrumental color parameters (brightness, redness, and yellowness). Organoleptic assessment found that raw PSP3 samples were harder, while cooked samples exhibited greater hardness but reduced springiness and juiciness compared to raw meat. In conclusion, incorporating PSP into chicken diets offers a sustainable solution for reducing environmental waste without adversely affecting growth performance, organ weights, or meat quality. This approach underscores the potential of agricultural by-products in animal nutrition.